2021
DOI: 10.4178/epih.e2021027
|View full text |Cite
|
Sign up to set email alerts
|

Trends in food and nutrient intake over 20 years: findings from the 1998-2018 Korea National Health and Nutrition Examination Survey

Abstract: OBJECTIVES: We aimed to examine the current status and trends of food and nutrient intake in the Korean population over the past 20 years using the data from the Korea National Health and Nutrition Examination Survey (KNHANES).METHODS: We conducted a survey of 116,284 subjects over the age of one year in Korea, who participated in the KNHANES between 1998 and 2018. We collected data on the subjects’ intake for the day before using the 24-hour recall method. The annual percent change (APC) in the food groups an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
2
6
2
Order By: Relevance
“…Compared with this criterion, the pre-energy intake in our study was 1360.7 Kcal in the intervention group and 1423.8 Kcal in the control group; regarding nutrients, 227.5 and 236.5 g of carbohydrates and 49.9 and 51.6 g of protein were consumed by the intervention and control groups, respectively. This result is similar to the results of previous studies [ 35 , 36 ] investigating vulnerable older adults with reduced mobility. However, as a result of applying the senior-friendly diet, energy and protein significantly improved in the intervention group.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with this criterion, the pre-energy intake in our study was 1360.7 Kcal in the intervention group and 1423.8 Kcal in the control group; regarding nutrients, 227.5 and 236.5 g of carbohydrates and 49.9 and 51.6 g of protein were consumed by the intervention and control groups, respectively. This result is similar to the results of previous studies [ 35 , 36 ] investigating vulnerable older adults with reduced mobility. However, as a result of applying the senior-friendly diet, energy and protein significantly improved in the intervention group.…”
Section: Discussionsupporting
confidence: 92%
“…Studies using the fifth KNHANES dataset reported the meat and alcohol patterns using a traditional method for dietary pattern extraction ( 12 ). Kweon et al ( 18 ) reported a decrease in the intake of grains, vegetables, and carbohydrates and an increase in the intake of beverages (sugar-sweetened beverages), meat, dairy, eggs, and fat. Furthermore, they reported an increase in the intake of snacks, frequency of dining out, and consumption of convenience foods over the past 20 years from the KNHANES datasets between 1998 and 2018, which have similar trends to our results.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, magnesium is particularly abundant in vegetables, fruits, and whole grains [ 4 29 ]. In Korea, the consumption of these foods has been observed to be on the decrease over the past 2 decades [ 9 ] and, contrary to this, the dietary share of highly processed foods has increased in the Korean diet [ 39 ]. The refining and processing of food results in a loss of the original magnesium content of the food [ 40 ], and the minerals content of processed foods such as ready-to-cook foods fails to meet the recommended intake [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported that a substantial number of Korean adults did not achieve the estimated average requirement (EAR) [ 4 7 8 ]. Along with a reduced consumption of magnesium-containing vegetables and fruits and increased consumption of magnesium-depleted refined or processed foods [ 1 9 ], the problem of inadequate magnesium intake is likely to be more serious. Low dietary magnesium intake has been linked to high risks of metabolic syndrome [ 10 ], hypertension [ 2 ], stroke [ 11 ], cancer [ 12 ], depression [ 13 14 ], and mortality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%